The functional support of special performance of female canoe paddlers in China - Gao, X.; Diachenko, A.; Rusanova, O. (National University of Ukraine on Physical Education and Sport, 2020)
At the present stage, the object of special attention is the women's canoe, a new kind of rowing competition. The popularity of the new type of the competition, the high level of the competition, and as a consequence, the intensity of the competition create requirements for the level of functional readiness of female athletes, in particular for the effective energy supply of work at a distance of 200 m (single) and 500 m (two).Currently, in the process of controlling, the characteristics of the functional readiness of women-rowers in canoeing are focused on the criteria of evaluating women's kayaks. Traditionally, the determination of a physical profile in a given sport involves the use of predictive testing as a measure of power and strength, speed, aerobic fitness or flexibility [1].Traditionally, the research in kayaking is primarily focused on athletes` physiological testing in order to determine fitness levels and then designing training programs to optimize physiological fitness [2]. Early studies only analysed VO2max to monitor and assess the physiological capacity of elite kayakers [3]. Nevertheless, the measurement of paddlers` maximal oxygen uptake is not the only possible determinant of performance. While characteristics of the sport demand that kayakers paddle most of the race at or around peak VO2, requiring high aerobic power, the anaerobic aspects should not be overlooked [4]. The previous research had significantly indicated higher VO2max levels than those observed here in both ergometer and treadmill tests, reporting values not lower than 54 ml/kg·minin either case [5]. However, any kind of comparison between studies must be carefully regarded due to the different protocols applied to estimate Oxygen uptake. Elite kayakers demonstrate superior aerobic and anaerobic quantities and have reported maximal oxygen consumptions of around 58 ml/kg·min (4.7 L/min) and lactate values of around 12 mM during laboratory and on water testing [3]. The literature on functional preparedness comprises small information on the specificity of energy supply and performance characteristicsin women's canoe [5]. All this does not allow to evaluate and interpret indicators as model characteristics of preparedness and use in the process of managing rowers' physical fitness.